Associação entre hemípteros e a presença de formigas em culturas agrícolas - Machado, Laura Magnani [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
O controle biológico em culturas agrícolas é tema de diversos estudos que demonstram o seu menor impacto ambiental e maior eficiência, quando comparado aos métodos tradicionais de controle de pragas. Algumas espécies de formigas são consideradas pragas, mas nos últimos anos, são estudadas como potenciais agentes de controle biológico, trazendo benefícios aos ecossistemas nos quais estão presentes. Essa ação benéfica está associada ao mutualismo entre as formigas e insetos hemípteros (Hemiptera) sugadores de seiva das plantas, produtores de um fluído açucarado (“honeydew”) atrativo e nutritivo às suas mutualistas, que, por sua vez, monopolizam a fonte alimentar e, consequentemente, protegem a planta de outras possíveis pestes. O forrageamento de formigas em populações de hemípteros pode causar tanto o crescimento quanto a diminuição do número de indivíduos de sugadores por planta hospedeira. Este trabalho consistiu em uma revisão sistemática sem restrição temporal da associação entre os hemípteros e a presença de formigas em culturas agrícolas. Os resultados revelaram uma ampla variedade de associações entre formigas, hemípteros e plantas diferentes ao redor do mundo. Com o emprego da meta-análise evidenciou que, no geral, a presença de formigas em colônias de hemípteros aumenta o número de sugadores por planta hospedeira, tendo impactos no uso de formigas como organismos de controle biológico de pragas agrícolas.

Biological control in agricultural cultures is the theme of many studies which demonstrate its minor environmental impact and better efficiency when compared to the traditional methods for plague control. Some ant species are considered plagues, but, in the last years, are studied as potential biological control agents, bringing benefits to the ecosystems in which they are present. This beneficial action is associated with the mutualism between the ants and sap-sucking hemipterans (Hemiptera), producers of a sugary fluid named honeydew, which is attractive and nutritional to their mutualists, that monopolize the food source and, consequently, protect the host plant from other plagues. The presence of ants foraging hemipteran populations may cause its growth or diminish the number of individuals per plant. This work consisted in a systematic review of the association between the hemipterans and the presence of ants in agricultural cultures. It revealed a large variety of associations between different ants, hemipterans, and ants around the world. A quantitative analysis of growth rates showed that the presence of ants increases this rate for hemipteran colonies, depending on the ant-hemipteran association. A meta-analysis showed that, in general, the presence of ants in hemipteran colonies raise its number per plant, impacting the use of ants as organisms of biological control of agricultural plagues, as a major quantity of hemipterans may have a beneficial effect on ant recruitment, which provide a protection against parasitoids and other plagues to the host plant.
Association between hemiterans and the presence of ants in agricultural cultures
Keywords: Entomologia; Revisão; Hemíptera; Formiga; Mutualismo